La pratique de terrain d’un géographe moderne, Albert Demangeon (1872-1940) - Denis Wolff (Belgeo)
While geographers of previous generations were specialists of historical geography, which is (exclusively) geography carried out from the study, Paul Vidal de la Blache and his followers were ardent promoters of fieldwork geography. One can reflect, however, on the meaning and modalities of this fieldwork approach so often invoked. This is what is attempted in this article that focuses on the geographer Albert Demangeon, relying on archival sources.Following a presentation of the archival sources used in this account, Demangeon’s individual practice is discussed, considering the size of the region under scrutiny, but also the geographer’s projects and the kind of research output aimed at... Regarded by him and his readers as the condition of validity of a piece of geographical work, the way he studies places (itineraries and objects of interest) conforms to his main objective: identifying and delineating regional physionomies. Are especially singled out: concerning physical geography, a certain interpretative model; concerning human geography, the importance of questionnaires as guidelines for research. Fieldwork is also a shared practice: it is at the same time about transmitting results to fellow geographers and about discussing them in situ - especially during interuniversity fieldtrips -, but also about “teaching the field” to students.